1962
DOI: 10.1002/zaac.19623150310
|View full text |Cite
|
Sign up to set email alerts
|

Über die Umsetzung von Wolframoxidtetrachlorid mit organischen Verbindungen

Abstract: IiihaltsubersichtEs werden die Umsetzungen des Miolframoxidtetrachlorids mit einer Anzahl sauerstoff-und stickstoffhaltiger organischer Verbindungen untersucht und die Reaktionsprodukte beschrieben. SummaryReactions of tungsten oxidetetrachloride with a number of oxygenand nitrogencontaining organic compounds have been investigated. The reaction products are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1965
1965
2005
2005

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…for C 6 There is, however, a distinct lack of information available on the preparation of phenoxide complexes derived from tungsten oxytetrachloride (WOCI4). [24] showed that mono-and bis-phenoxide complexes could be prepared from WOCI4 and salicylic acid, salicylaldehyde or methyl salicylate. By employing quite harsh reaction conditions, Prasad and coworkers …”
Section: Methodsmentioning
confidence: 99%
“…for C 6 There is, however, a distinct lack of information available on the preparation of phenoxide complexes derived from tungsten oxytetrachloride (WOCI4). [24] showed that mono-and bis-phenoxide complexes could be prepared from WOCI4 and salicylic acid, salicylaldehyde or methyl salicylate. By employing quite harsh reaction conditions, Prasad and coworkers …”
Section: Methodsmentioning
confidence: 99%
“…The reaction between WOCl 4 and salicylic acid was reported by Funk, 12 who performed melt reactions at the melting point of salicylic acid (ca. 160 • C) and proposed the formation of several compounds on the basis of elemental analysis.…”
Section: Introductionmentioning
confidence: 91%